The Training and Assistance of Writing Scientific Articles to National Journal of Sinta for Certified School Teachers at Lampung Province - Ikhwan Aziz Q; M. Sayyidul Abrori; Riyadul Falahul Imam (Yayasan Payungi Smart Madani, 2022)
This dedication is motivated by the lack of skills and experience of school or madrasah teachers in writing scientific articles. Therefore, PKM training and assistance in writing scientific articles and submissions in reputable National Journals for school or madrasah teachers is very necessary and important. The purpose of this service is to train teachers to develop skills in writing scientific articles and submitting to Sinta's reputable National Journal because one of the parameters for a teacher's rank is the publication of scientific articles. This study uses ABCD (Asset Based Community Development method). Five references for conducting this research are; discovery, dream, design, define, and destiny. The methods of this research include: the preparation stage which consists of observations, interviews with teachers, delivery of strategies, and material counseling, the implementation stage which consists of the implementation of socialist activities that begin with the approach and mentoring of teachers, the evaluation stage of the assessment of the activities that have been carried out. The result of this service will be that the teacher is able to write scientific articles and submissions well. Then the implication of this service is as a reference by education practitioners to improve teacher skills in writing scientific articles and submissions to the reputable National Journal of Sinta.